Predictability of parental ultraviolet-B environment shapes the growth strategies of clonal Glechoma longituba - Guo, Yuehan; Quan, Jiaxin; Wang, Xubo; Zhang, Zhixing; Liu, Xiao; Zhang, Ruichang; Yue, Ming (Frontiers in Plant Science, 2022)
Although there is an increasing debate about ecological consequences of environmental predictability for plant phenotype and fitness, the effect of predictability of parental environments on the offspring is still indefinite. To clarify the role of environmental predictability in maternal effects and the growth strategy of clonal offspring, a greenhouse experiment was conducted with Glechoma longituba. The parental ramets were arranged in three UV-B conditions, representing two predictable environments (regular and enhanced UV-B) and an unpredictable environment (random UV-B) respectively. The offspring environments were the same as their parent or not (without UV-B). At the end of experiment, the growth parameters of offspring were analyzed. The results showed that maternal effects and offspring growth were regulated by environmental predictability. Offspring of unpredictable environmental parents invested more resource in improving defense components rather than in rapid growth. Although offspring of predictable parents combined two processes of defense and growth, there were still some differences in the strategies between two offspring, the offspring of regular parent increased the biomass allocation to roots (0.069 g of control vs 0.092 g of regular), but that of enhanced parent changed the resource allocation of nitrogen in roots and phosphorus in blade. Moreover, when UV-B environments of parent and offspring matched, it seemed that maternal effects were not adaptive, while the growth inhibition in the predictable environment was weaker than that in unpredictable environment. In the predictable environment, the recovered R/S and the increased defense substances (flavonoid and anthocyanin) contributed to improving offspring fitness. Additionally, when UV-B environments of parent and offspring mismatched, offspring growth was restored or improved to some extent. The offspring performance in mismatched environments was controlled by both transgenerational effect and within-generational plasticity. In summary, the maternal effects affected growth strategies of offspring, and the differences of strategies depended on the predictability of parental UV-B environments, the clone improved chemical defense to cope with unpredictable environments, while the growth and defense could be balance in predictable environments. The anticipatory maternal effects were likely to improve the UV-B resistance.